The application of Shariah principle in e-commerce transaction: a model development - Mohd Zulkifli Muhammad; Tamrin Amboala; Muhammad Zulfaris Mohd Salleh; Azwan Abdullah; Siti Nurzahira Che Tahrim; Noorshella Che Nawi (Sciedu Press, 2019)
Issues concerning purchasing on-line, the medium of transaction via on-line or Internet, e-payment mode are among new challenges that require Islamic scholars and researchers to broaden the scope of definition of Shariah compliance e-commerce transaction. As Malaysia is heading towards e-commerce and purchasing on-line has no longer a new trend; the challenges arise for solution in accordance with Shariah principles. This paper will propose a model that comprises several components namely, the core Shariah component itself, sound technological means and regulatory body that supports e-commerce transactions